Studying the Impact of Auditors' Anxiety on Auditor's Report Content - Gharicheh, Mansoreh Zarrin; Baradaran Hasanzadeh, Rasoul (Social Determinants of Health, 2021)
Backgound: Auditors face a wide range of expectations due to conflict of interest between managers and investors that causes stress in the audit work and may have a significant impact on the quality of the audit. Methods: This cross-sectional study was performed on 585 signatories of the audit reports of 139 companies listed on the Tehran Stock Exchange in 2016 and 2017. The statistical population of the study was the signatories of the audit report of the accepted companies in Tehran Stock Exchange. In present study, the information about anxiety of audit managers was collected using Beck Anxiety Questionnaire (1988) and multiple regression and logistic models were used to test the hypotheses. Results: In this study, 585 auditors were examined. The results shown auditors' anxiety leads to presenting an acceptable report and a smaller number of condition clauses, but it does not affect the type of clause and the number of opinion clauses. The results show that auditors who are not anxious or are slightly anxious 371(63.4%) cases do not find themselves under the pressure of negligence of the client, but auditors with moderate anxiety 228 (39%) cases are more probably tend to present acceptable reports and therefore fewer condition clauses due to fear of losing their job. Conclusion: As this study showed auditor's anxiety has no effect on the type of condition clause and also the number of clauses after the opinion; while auditors' anxiety affects the type of auditors' opinion and the number of condition clauses.